Pengaruh Model Kooperatif Tipe Scrable Berbantuan Media Card Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas V dan SDIT Almawaddah Warahman Kolaka - Apriliah, Nurfadillah; Risani, Arni; Muslim, Muslim; A.Arif, Tarman (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to analyze the effect of the scramble type cooperative model assisted by media cards on student learning outcomes in mathematics learning in class V MI and SDIT Almawaddah Warrahman Kolaka. This study is a quantitative study with a quasi-experimental design. The population of the study was all students of class V MI and SDIT Almawaddah Warrahman Kolaka totaling 15 students. The research instuments included a learning outcome test sheet (a written test in the form of an essay of 10 questions about multiplication) and an observation sheet to observe the learning process of teachers and students using media cards. Data collection techniques used tests (pretest and posttest) and observation. Data analysis was carried out descriptively and inferentially using SPSS 25, including normality tests, homogeneity tests, and hypothesis tests. The results showed that the average posttest score of the experimental class (cooperative model scramble type assisted by media cards) was 91,84 higher than the control class (classical learning expository technique) with an average of 86.31. the normality test showed that the pretest dan posttest data of both classes were normally distributed. The homogeneity test also shows that the variance of the pretest and posttest data of both classes is homogeneous. The results of the hypothesis test using the Independent Sample T-Test show a Sig value of 0,045, which is smaller thean 0,05. This indicates that H0 is rejected and H1 is accepted, indicating a positive influence of the scramble type cooperative model assisted by card media on student’s mathematics learning outcomes.